Identification of hub genes and pathways in mouse with cold exposure - Wang Xu; Hu Hongbo; Zhang Ying (Frigid Zone Medicine)
Cold exposure is linked to numerous diseases, yet the changes in key genes and pathways in mice under cold exposure remain unexplored. Understanding these alterations could offer insights into the mechanisms of cold resistance and contribute valuable ideas for treating cold-related diseases.